Chrysis fuscipennis or Chrysis angolensis? An answer with new synonymies, a new combination and species resurrected (Hymenoptera, Chrysididae) - Paolo Rosa (Journal of Entomological and Acarological Research, 2024)
All species of the Chrysis angolensis group were synonymised with C. angolensis Radoszkovsky, 1881, excluding Chrysis diademata Mocsáry, 1889, endemic of the Philippines. However, after the study of type materials, four species are herein resurrected: Chrysis callaina Gribodo, 1884 stat. reviv., C. erratica Abeille de Perrin and du Buysson in du Buysson, 1887 stat. reviv., C. mossulensis Abeille de Perrin and du Buysson in du Buysson, 1887 stat. reviv., C. sulcifera Bischoff, 1910 stat. reviv. New synonymies are proposed for the following taxa: C. szalayana Mocsáry, 1912 n. syn. and C. ukerewensis Mocsáry, 1914, n. syn. of C. callaina Gribodo, 1884; Chrysis janthina Smith, 1874 n. syn. of C. brachyceras Bischoff, 1910. The new combination Praestochrysis brachyceras (Bischoff, 1910) n. comb. is proposed. Chrysis fuscipennis Brullé, 1846, the name in use for the oldest taxon described in the angolensis group, was replaced with Chrysis angolensis Radoszkovsky, 1881 because primary junior homonym of C. fuscipennis Dahlbom, 1829. However, Chrysis angolensis is here regarded as nomen dubium, C. fuscipennis Dahlbom, 1829 as nomen oblitum, because no longer in use as a valid name after 1899, and C. fuscipennis Brullé as nomen protectum, thus making the name C. fuscipennis Brullé, 1846 stat. reviv. available and restored.